1 Kings 12-22 - Maier, Walter A, III, 1952- (Saint Louis : Concordia Publishing House, 2019)
This volume continues Dr. Maier's exposition of the text of 1-2 Kings, which is a history, written in a selective manner, for the sake of theology. This history of Israel covers over three hundred and eighty years by focusing primarily on one aspect: that of the monarchy, from the last part of David's rule to the end of the kingship in Judah with an added note concerning the exiled Judean king. 1 Kings 12-22 covers the period from the division of the monarchy after the death of Solomon up to the reign of Ahaziah. Along with its attention to the kings of Israel, this history also emphasizes prophets, who were contemporaries of these rulers and who interacted with them. The purpose of 1-2 Kings is not only to record for posterity certain events which actually took place, but also to convey theology. In particular, this history presents God--the holy, righteous, just, merciful, compassionate, gracious, omnipotent, and omniscient Deity--in relationship with Israel (from the tenth to the sixth centuries BC). --
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries